Academic program development: a collaborative and context-sensitive approach - Michele A. Parker; Tamara M. Walser; Satlaj Dighe (Discover Education, 2024)
Abstract This perspective paper describes the strategic development of evaluation and organizational learning programs focused on building core knowledge and skills at a university with high research activity. New program development allows academic leaders to introduce relevant and cutting-edge knowledge to students. Nevertheless, the program development process must be more explicit, as it faces many logistical and technical challenges. We argue that academic program development needs to be an integrated and collaborative process paying intentional attention to program needs, context, mission, student learning outcomes, and program of study. The article describes our experiences implementing these processes, explains the interrelationships between the processes, and shares our perspective on academic program development. Our story began with establishing a faculty team and conducting literature reviews to identify gaps in existing evaluation education programs. The interest surveys indicated that 46% of the respondents are interested in pursuing an advanced degree. In addition, 88% of employers and supervisors indicated their preference for a master’s degree in evaluation. Forty-two percent of the respondents also pointed to a strong interest in an online program. The program team used this survey data to determine the next steps for program development. Finally, the paper contends that a collaborative stance is central to academic program development. The paper describes our approach to building solid collaborations with students, prospective employers, leadership at the department, college, and university levels, and vocational organizations. Through our program development experience, we advocate for adopting a systematic, collaborative, and context-sensitive approach to program development.